PENGAMANAN TEKS PADA DOKUMEN EMAIL MENGGUNAKAN ENKRIPSI ROTOR - Arfriandi, Arief (Jurusan Teknik Elektro Universitas Negeri Semarang, 2018)
The delivery of a letter electronically are very popular the last few years, so many people utilize to send important documents to the destination. Electronic mail that is commonly referred to by email, use the internet access in its operation. The email when sent, realistically not up to the destination but kept on the server the owner of email services. After the email is saved to the server then the email can be read by the destination written email account when sending email. When data or documents stored on the server can be potentially exploited by the email service providers without the permission of the owner of the data, it is certainly a security issue related to the data confidentiality of the data. To maintain the confidentiality of such data, one of the methods that is believed to be able to cope with it is Cryptography. In this study, researchers developed a technique of securing text on document email using cryptography method with rotor encryption. Research methods used were derived from a review of the literature to find out the model of the safeguards text in the document. Then analyze the weaknesses of earlier related research based pengemanan the text of the document. The next step is followed by the design of the rotor encryption implementation on the text message and continues to perform calculations using rotor encryption on the text of the document to be sent via email. The results of securing the text in documents that will be sent via email, is expected to enhance the confidentiality of data when stored on the server.